Preparation and characterization of BaBi2Nb2O9(BBN) ceramics synthetized by polymeric precursors method - Campos, A. L. [UNESP]; Mazon, T. [UNESP]; Varela, José Arana [UNESP]; Zaghete, M. A. [UNESP]; Cilense, M. [UNESP] (Trans Tech Publications, 2001)
Pure BBN powders and with addition of 1 and 2 wt% in excess of bismuth were obtained by Pechini Method. The powders calcined at 300°C/4h were analyzed by TG/DTA to study the temperature of organic matter decomposition. A systematic study of calcination temperature and time to the formation of the BBN phase was performed and the phase formation was accompanied by XRD. The calcined powders at 800°C during 2h were analyzed by infrared spectroscopy and by BET. The powders were isostaticaly pressed and sintered at temperatures ranging from 900°C to 1000°C. The ceramics were characterized by XRD to control the crystalline phase and by SEM to analyze the microstructure.
Keywords: Barium compounds; Calcination; Crystal microstructure; Crystalline materials; Differential thermal analysis; Infrared spectroscopy; Powders; Scanning electron microscopy; Sintering; Synthesis (chemical); Thermogravimetric analysis; X ray diffraction analysis; Crystalline phase; Pechini method; Ceramic materials